Các kết cấu phi ngoại động trogn tiếng Việt - Cổn, Nguyễn Hồng (VNU Journal of Science: Social Sciences and Humanities; Vol 20 No 1, 2004)
The paper explores the typology of de-transitive constructions in Vietnamese. These are N2 -V constructions which are formed from the active-transitive constructions (Ni - V- N2) by three transformation devices: detopicalization of the agent (Nl), topicalization of a non agent argument (N2), and stativization of the predicative verb (V). Their surface forms are similar to the passive constructions, but they do not have passive markers of được and/or bị. Through the analysis of their semantic structures and grammatical behaviors, the paper suggests that these constructions may be considered as different typolopies of de-transitive constructions in Viet.nam.se: active de-transitive constructions, pocessive de-transitive constructions and stative de-transitive constructions.